The South China Sea Disputes in International Law Perspective (The Digest: Journal of Jurisprudence and Legisprudence, 2021)
The South China Sea issue is getting worse. China's claims overlap with those of other parties such as Vietnam, the Philippines, Malaysia and Brunei. To defend its claim, China is trying to dominate, both in the disputed territory and in multilateral negotiations. In the disputed territory, China seized the area, carried out reclamation, and attacked ships in other countries under various pretexts. Until the Philippines finally brought the dispute to the Permanent Court of Arbitration. The decision of the Permanent Court of Arbitration said that China's claims regarding the nine dash lines were indisputable and had no legal basis. The decision of the Permanent Court of Arbitration. Which was a source of international law was rejected by China. This article aims to describe the validity of the Permanent Court of Arbitration decision if the decision is rejected by one party based on the perspective of international law.